2020
DOI: 10.1128/msystems.00098-20
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Assembly Processes Are Coordinated between Bacterial and Viral Communities in Fractured Shale Ecosystems

Abstract: The ecological drivers that concurrently act upon both a virus and its host and that drive community assembly are poorly understood despite known interactions between viral populations and their microbial hosts. Hydraulically fractured shale environments provide access to a closed ecosystem in the deep subsurface where constrained microbial and viral community assembly processes can be examined. Here, we used metagenomic analyses of time-resolved-produced fluid samples from two wells in the Appalachian Basin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…Having a common conceptual grounding across studies provides an opportunity to investigate assembly processes affecting metabolite assemblages, and to develop theory that applies across and within ecosystems and spatiotemporal scales. Moreover, this common theory can be used to study ecological communities (e.g., microbes) and the metabolites they transform using the same framework, as previously performed with bacteria and viruses 78 . The degree of coordination between assembly processes can be subsequently related to microbial processes, DOM components, and environmental factors to reveal variables important to convergent and divergent assembly, in turn providing insight into those factors underlying biogeochemistry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a common conceptual grounding across studies provides an opportunity to investigate assembly processes affecting metabolite assemblages, and to develop theory that applies across and within ecosystems and spatiotemporal scales. Moreover, this common theory can be used to study ecological communities (e.g., microbes) and the metabolites they transform using the same framework, as previously performed with bacteria and viruses 78 . The degree of coordination between assembly processes can be subsequently related to microbial processes, DOM components, and environmental factors to reveal variables important to convergent and divergent assembly, in turn providing insight into those factors underlying biogeochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…While we focused heavily on dendrogram-based null models, there are other immediate opportunities to advance understanding by combining dendrogram-based and dendrogram-free null models. This approach has been pioneered in microbial ecology to parse out the relative influences of variable selection, homogeneous selection, dispersal limitation (combined with drift), and homogenizing dispersal (i.e., mass effects) 35 , 64 , 78 , 81 . More specifically, this is pursued by combining the βNTI null model with the identity-based Raup–Crick null model.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in DNA sequencing technology in the last 2 decades ( 25 ), paired with the more recent implementation of community assembly theory and modeling of sequencing data from microbial ecosystems, have provided new insights into the mechanisms that structure microbial communities in a variety of conditions ( 24 , 26 36 ). Assessments of community assembly in groundwater systems have shown that selection and dispersal processes play an extremely important role in structuring both the environmental resource landscape as well as microbial communities ( 29 , 31 , 32 , 34 , 37 ). Due to accessibility, much of this work has been performed in neutral pH, near surface, groundwaters with connectivity to the surface ( 31 , 32 , 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to accessibility, much of this work has been performed in neutral pH, near surface, groundwaters with connectivity to the surface ( 31 , 32 , 37 ). Relatively little work has been done in isolated hard-rock aquifers within the deep subsurface ( 29 , 34 ). Old groundwaters (>100 years), which are often hosted within hard-rock aquifers in the deep subsurface, are a substantial reservoir of globally available freshwater ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation